A New Species of Eriosema (Leguminosae, Papilionoideae, Phaseoleae) from the savannas of northern South America - Campos, Renan Pavan [UNESP]; Cândido, Elisa Silva; Zeferino, Laís Couto [UNESP]; Fortunaperez, Ana Paula [UNESP] (Magnolia Press, 2023)
During a taxonomic study of the species of Eriosema in South America, a new species was discovered, occurring in the savannas of northern South America. Eriosema parvifolium is here described and illustrated and its morphological similarities with its closest relatives are presented. The geographical distribution, conservation status, and information about flowering and fruiting are provided. Additionally, a dichotomous key to the taxa of Eriosema that occurs in savannas region of northern South America was made.
Keywords: Cajaninae; Fabaceae; South America savannas; taxonomy